Analysing Factors Affecting Implementation of Automated Construction Progress Monitoring in Indian Construction Industry - Mohd Sameer Malik; Dr. M. Kranti Kumar, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
Automated construction progress monitoring has evolved as a critical element in modern construction projects, increasing efficiency and decision-making processes. It has gained recognition as a revolutionary technology in the global construction industry. However, its successful implementation in India presents distinct problems driven by a variety of factors such as technological challenges, financial restrictions, a shortage of qualified labour, resistance to technology adoption, a high initial investment, and so on. This research explores the importance of automated construction progress monitoring, examines the factors that influence its adoption, and makes recommendations for its implementation in the Indian construction industry. By recognising these variables, construction stakeholders can better negotiate the hurdles and reap the benefits of automated monitoring technology.